Dehydration of jambolan [Syzygium cumini (L.)] juice during foam mat drying: Quantitative and qualitative changes of the phenolic compounds - Iasnaia Maria de Carvalho, Tavares [UNESP]; Nogueira, Tuany Yuri Kuboyama [UNESP]; Mauro, Maria Aparecida [UNESP]; Gómez-Alonso, Sergio; Gomes, Eleni [UNESP]; Da-Silva, Roberto [UNESP]; Hermosín-Gutiérrez, Isidro; Lago-Vanzela, Ellen Silva [UNESP] (Elsevier, 2017)
Jambolan [Syzygium cumini (L.)] berries are a popular fruit in Brazil, renowned for their high phenolic compound (PC) content. These PCs have antioxidant, antibacterial, and other characteristics that may be beneficial to human health. The objective of the study was to evaluate the quantitative and qualitative changes of the main phenolic compounds (PCs) (anthocyanins, flavonols, and hydrolysable tannins) in the jambolan fruit, the produced fruit juice, and in the corresponding dehydrated powders obtained by foam mat drying (60, 70, and 80 °C) and lyophilization (control). The PCs were analyzed using high-performance liquid chromatography with a diode array detection coupled with an electrospray ionization mass spectrometry (HPLC-DAD-ESI-MSn). Juice production resulted in a more pronounced degradation of anthocyanins than flavonols, and facilitated the extraction of hydrolysable tannins. Elevation of the dehydration temperature negatively impacted the anthocyanin content of the products; on the other hand, the flavonols and hydrolysable tannins were more sensitive to oxidation and heating time during dehydration, respectively, than dehydration temperature. In summary, it can be concluded that processing at 70 °C is most suitable, in light of the least loss of nutritional quality of the product with processing time. This study directly informs further investigations into preparation of high-quality jambolan fruit products.
Keywords: Anthocyanins; Antioxidant activity; Flavonols; Foam mat drying; Hydrolysable tannins; Jambolan; Juice; Phenolic compounds